Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.15698/mic2023.03.793
|View full text |Cite
|
Sign up to set email alerts
|

D-Serine reduces the expression of the cytopathic genotoxin colibactin

Abstract: Some Escherichia coli strains harbour the pks island, a 54 kb genomic island en-coding the biosynthesis genes for a genotoxic compound named colibactin. In eukaryotic cells, colibactin can induce DNA damage, cell cycle arrest and chro-mosomal instability. Production of colibactin has been implicated in the devel-opment of colorectal cancer (CRC). In this study, we demonstrate the inhibito-ry effect of D-Serine on the expression of the pks island in both prototypic and clinically-associated colibactin-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…d-Serine can be obtained through dietary sources, such as fermented and fortified foods, or by conversion from l-Serine. Recent work by Hallam et al, (2023) has shown that d-Serine downregulates colibactin synthesis and reduces subsequent genotoxicity [96]. Repression of clb genes by d-Serine was found to be independent of the serine tolerance locus dsdCXA and the exact mechanism of d-Serine-induced clb gene repression still remains to be elucidated.…”
Section: D-serinementioning
confidence: 99%
See 2 more Smart Citations
“…d-Serine can be obtained through dietary sources, such as fermented and fortified foods, or by conversion from l-Serine. Recent work by Hallam et al, (2023) has shown that d-Serine downregulates colibactin synthesis and reduces subsequent genotoxicity [96]. Repression of clb genes by d-Serine was found to be independent of the serine tolerance locus dsdCXA and the exact mechanism of d-Serine-induced clb gene repression still remains to be elucidated.…”
Section: D-serinementioning
confidence: 99%
“…Repression of clb genes by d -Serine was found to be independent of the serine tolerance locus dsdCXA and the exact mechanism of d -Serine-induced clb gene repression still remains to be elucidated. It is possible that d -Serine, or a subsequent metabolic product of its catabolism, may act as a cofactor to a transcriptional regulator of the pks island [ 96 ].…”
Section: External Inputsmentioning
confidence: 99%
See 1 more Smart Citation